Answers

2016-06-20T20:48:14+08:00
First step:    assume that the first term is   24
                   also the number of terms from the second to the fifth                              term  =   (5-2) + 1   =   4
second step:   use  formula      n term   =   a + (n-1)d  where a  
                                       = first  term &  n =  number of terms
                       thus        3  =  24 + ( 4-1)d  
                                     3  =  24 + 3d
                                      3d =  -21
                                         d =   -21/3     = - 7
        answer:   first term   =   31    and  common difference d = -7
0